Use of antidepressant treatment. Patients' perception - Martín, M. J.; García-Toro, M.; Campoamor, F.; Pareja, A.; Aguirre, I.; Salvá, J.; Roca, M. (Actas Españolas de Psiquiatría, 2009)
Introduction. A major determinant of response to antidepressant drugs is how the patients use them. Our objective is to take a look over the antidepressants use in a real sample. Methods. In determining which factors may be relevant for treatment good use, social, demographic, disease and treatment-related data were gathered from 550 patients, who were currently taking antidepressants for any motive. The questionnaire included two items, the patients' perceived difficulty of following treatment and the level of acknowledged non-compliance by the patient, which may be considered as both an indirect and guiltless way of approximating the patients' real use of treatment. Results. Compliance was poor among the less educated, as well as those living in rural areas and in patients receiving concomitant treatment for organic diseases. Use was good in 61.5% and was particularly good among those with an affective disorder (69.8%). Among patients who did not respond to treatment, the incidence of non-compliance (49.1%) was higher than for those achieving improvement (31.2%). Conclusions. It's important to explore and reinforce a good use of antidepressants in clinical settings and to be sure this type of treatment is necessary if the indication is not clear.